Usulan Perawatan Sistem Boiler dengan Metode Reliability Centered Maintenance (RCM) - Hamim Rachman; Annisa Kesy Garside; Heri Mujayin Kholik (Department Industrial Engineering, University of Muhammadiyah Malang, 2017)
Pembangkit Listrik Tenaga Uap (PLTU) PT Indo Pusaka Berau is a PLN work unit that provides electricity to consumers. The problem of the company is the frequent damage to boiler engine components. The company uses corrective maintenance system. On the problem, it is necessary to develop a machine maintenance system with Reliability Centered Maintenance (RCM) approach. The objective of the study was to select a boiler system maintenance action based on the RCM method and component replacement interval to minimize Total Minimum Downtime (TMD). Results of data processing RCM method, component in category Condition Directed (CD) is El Bow component. Components in Time Directed category (TD) are gland seal steam and check valve. Components in the Time Directed category are calculated for component replacement intervals on TMD criteria. The calculation result from component replacement interval was obtained 37 days for gland seal steam component and 58 days for check valve component. The proposed treatment of RCM method can reduce downtime by 11.33% of the company's maintenance methods.